International research on labor in agri-food value chains: A bibliometric review from web of science - Malanski, Priscila Duarte; Schiavi, Sandra Mara de Alencar; Dedieu, Benoît; Damansceno, Julio César (Frontiers in Sustainable Food Systems, 2022)
Value chains are an important driver for the current labor dynamics in the agri-food sector, and agri-food value chain sustainability strongly depends on decent work conditions. An increasing literature body have been investigated the interactions between chain agents and how it impacted labor issues. Our aim was to map the scientific landscape of the scientific knowledge on labor in agri-food value chains. We performed a bibliometric review of 343 articles indexed in the Web of Science based on descriptive and network analysis of articles metadata, which covered authors, journals, citation times, keywords and countries. We showed that labor in agri-food value chains has an international audience, despite that knowledge production was largely built by a restraint leading scientific network. Overall, the scientific knowledge is organized into four main research domains on labor in agri-food value chains: 1) labor governance in global value chains through standards, 2) employment in value chains and impacts on socioeconomic conditions of rural areas, 3) gender issues and value chains, 4) labor and upgrading in global value chains. The controversies in the international literature regarding labor issues in the agri-food value chains, and blind spots of current research are discussed.